Role of anti-oxidants to reduce free radical induced injury in preeclampsia - Tripathi, Nidhi; Singh, Amrita; Pandey, Kiran; Singh, Neetu; Arya, Sangeeta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: The aim of study is to study role of antioxidants to reduce free radical induced oxidative stress in preeclampsia. Methods: A prospective study conducted with 326 patients in UISEMH, Kanpur at Department of Obstetrics and Gynaecology from January 2011 - January, 2012 with 326 patients. There were divided into 2 groups - control and study group on the basis of measurement of activity of superoxide dismutase at 20 weeks, control group constituted patients with normal SOD level (Normal values >0.702 U/mg of protein). Study group constituted 180 patients with decreased SOD level at 20 weeks, they were further divided into 2 groups - study group A and study group B, according to intervention given in form of Vit. C 1000 mg OD from 20 weeks till delivery. SOD was re-measured in control and study group at 32 weeks. Result was studied in terms of value of SOD at 32 weeks and incidence of PIH and IUGR, mode of delivery, complications in forms of mild and severe PET, Abruptio placentae, antepartum eclampsia and IUGR. Results: The study showed that mean level of SOD at 20 weeks in study group was much less as compared to control group, also SOD value in group A at 32 weeks is much less as compared to group B in which intervention was given t value ~ 46.877, p value <0.0001; 95% CI - 0.285223 - 0.310391, which is statistically highly significant. Hence, in our study there was statistically significant improvement in SOD enzyme levels after giving intervention in study group. Conclusions: Since, preeclampsia is multifactorial disorder in which oxidative stress plays very important role in pathophysiology amongst various other factors. The antioxidant supplementation to such patients who already have reduced anti-oxidant status definitely has role in decreasing incidence of PIH and its severity.